The Potential of Ethno-STEM Learning to Enhance Environmental Literacy: A Literature Review - Nadila Fetiana; Ina Ana Khoeriyah; Suriyani Suriyani (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2026)
This study aims to systematically review the use of local wisdom in Ethno-STEM learning, the types of learning models applied, and their potential to improve students' environmental literacy. A Systematic Literature Review (SLR) was conducted following the PRISMA framework and bibliometric analysis using VOSviewer. Initial data were obtained from 1,234 articles across three databases: Crossref (n=1000), Google Scholar (n=200), and Scopus (n=34). The articles were screened through identification, screening, eligibility, and inclusion stages, resulting in 15 studies that met the inclusion criteria. The reviewed articles were limited to publications within the 2021–2026 period. The results show that studies on Ethno-STEM have experienced an increasing trend, especially starting in 2021 with a greater focus on the integration of local wisdom in science learning. The analysis shows that local wisdom utilized in Ethno-STEM learning generally includes local cultural practices that have similar pedagogical, conceptual, and contextual characteristics. The implementation of Ethno-STEM learning based on local wisdom is dominated by the use of project-based learning models, in addition, Ethno-STEM learning based on local wisdom shows potential in improving students' environmental literacy which includes dimensions of knowledge, cognitive skills, attitudes, and behavior towards the environment